ANALISIS PEMBELAJARAN BERDIFERENSIASI MENGGUNAKAN MODEL PEMBELAJARAN TEAM GEMAES TOURNAMENT PADA MATA PELAJARAN IPAS DI KELAS V SD GMIT 25 FANATING - samma, rahmayani; Prasong, Muthiah; Asikin, Yakin (Jurnal Edukasi, 2026)
Rahmayani Samma.2025. "Analysis of Differentiated Learning Using the Team Games Tournament Learning Model in Science Subjects in Grade V of GMIT 25 Fanating Elementary School." This study uses a qualitative research method, because the researcher wants to describe a phenomenon according to the actual conditions experienced by the research subjects and present the data in the form of words. The purpose of the researcher in choosing this type of research is because the researcher wants to examine the condition of the natural object based on the results of observations, interviews, and documentation with the researcher himself as the key instrument. The results of this study are: (1) Analysis of Differentiated Learning Using the Team Games Tournament Learning Model in learning I and II has gone well, the implementation of Science I learning was carried out by the homeroom teacher of grade V while learning II was carried out by the researcher. In the implementation of learning I, the class teacher only applies the same learning repeatedly in each meeting which makes some students not understand the learning, and are slow in responding to learning so that the researcher applies the Team Games Tournament learning model, by implementing it, students are very interested, motivated, and enthusiastic in carrying out learning (2) Supporting factors and inhibiting factors for teachers in differentiated learning using the Team Games Tournament Learning Model in Science Subjects in Class V of GMIT 25 Fanating Elementary School, among the supporting factors are: Support from the Education Office and the School, which is expected to help and facilitate class teachers and subject teachers in implementing differentiated learning. While the inhibiting factors are: some class and subject teachers have not optimally understood the flow of learning objectives of the independent learning curriculum. and the lack of learning facilities and infrastructure that make teachers only adjust their learning to conditions in the classroom.